Unreported discards of internationally protected pelagic sharks in a global fishing hotspot are potentially large. (May 2022) - Mucientes, Gonzalo; Vedor, Marisa; Sims, David W.; Queiroz, Nuno
Abstract: Global abundances of oceanic pelagic sharks have declined due to overfishing. Internationally protected shark species remain at risk due to indiscriminate bycatch in longline fisheries with under-reported catches affecting reliability of population assessments for management. However, the scale of under-reporting remains poorly understood. Here we use detailed shark species catch data in a global fishing hotspot to show that the discards of three globally or regionally 'Endangered' or 'Critically Endangered' species (bigeye thresher Alopias superciliosus ; oceanic whitetip Carcharhinus longimanus ; smooth hammerhead Sphyrna zygaena ) are potentially under-reported on a large scale: the total discards made by a single observed vessel in April–June 2018 in the eastern tropical Atlantic exceeded by 1.3–11.0 times the discards reported officially for these species Atlantic-wide for all of 2018. Scaling up observed catches (discards) of a single vessel to potential discards made by a single nation's fleet in the region, we estimate a mean annual total of 1526.2 t (±1 S.D. range: 415.3–2637.0 t), which exceeds by 89.2 times (±1 S.D. range: 24.3–154.2 times) the official reported discards for these three species. Without reducing bycatch mortality, which at present appears obscured by substantial under-reporting, Atlantic populations remain at serious risk. Highlights: The scale of under-reporting of internationally protected shark species in pelagic longlines remains poorly understood. We showed that the total discards in a global fishing hotspot exceeded by 1.3–11.0 times the Atlantic-wide official reports. We further estimate a mean annual catch in the same general area of 1, 526.2 t, exceeding by 89.2 times the official reports. Without specific measures for reducing bycatch shark mortality, Atlantic populations remain poorly monitored and at risk.